Textbook on tort - Howarth, David (Butterworths, 1995)
With the apparently unpredictable nature of tort law expertly considered, this text gives a clear account of the most recent arguments commonly used by the courts and how they are developing from case to case. Reference is given to selected cases which illustrate these arguments and to those which are of inherent interest